GUIORA, A. N. Cybersecurity: geopolitics, law and policy. Boca Raton, FL: Routledge, ISBN: 978-1-315-37023-1, 2017, 170p. - Maier, Friedrich (Conjuntura internacional, 2018)
Resenha do livro: GUIORA, A. N. Cybersecurity: geopolitics, law and policy. Boca Raton, FL: Routledge, ISBN: 978-1-315-37023-1, 2017, 170p.